Budaya Komunikasi Masyarakat Desa di Era Industri 4.0: Studi Kasus Desa Astanamukti Kabupaten Cirebon - Diki Hadiyanto; Asep Mulyana; Nuryana Nuryana (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to describe the pattern of Communication Culture in the 4.0 Industrial Era among the community of Astanamukti Village, Pangenan District, Cirebon Regency, Indonesia. The focus of this study is the pattern of cultural communication that occurs in society, as well as social changes in society towards patterns of communication culture in the industrial era 4.0 and the impact of social change in the people of the village under study on cultural communication patterns. This study used descriptive qualitative research. The data source for this research were village officials, community leaders, youth leaders, and teachers. Data collection techniques used are observation, interviews, and documentation. Data analysis was carried out with the stages of data reduction, drawing conclusions, and checking the validity of the data. The study results show that the communication patterns in the Astanamukti Village community in the current 4.0 industrial era are widely varied, starting from an understanding of communication media which has begun to increase among the Astanamukti village community. Social changes occur in the economic, cultural, communication, and social sectors. The impact of social change on the village community includes positive and negative effects, which were also influenced by the presence of industrial development.